Global burden, trends, and inequalities in cancer and subtypes attributable to high BMI among older adults, 1990–2021: a secondary analysis of the global burden of disease study 2021 - Huang, Yitong; Qiu, Di; Xuan, Feng (Frontiers in Nutrition, 2025)
BackgroundHigh body mass index (BMI) is a significant modifiable risk factor for cancer, yet its global burden in older adults (aged ≥60 years) remains incompletely understood.MethodsUsing Global Burden of Disease Study 2021 data, we estimated disability-adjusted life-years (DALYs) and age-standardized DALY rates (ASDRs) for total and 11 high BMI-related cancers from 1990 to 2021. Trends were assessed using average annual percentage change. Inequalities were measured using the slope index of inequality and concentration index. Additionally, decomposition and frontier analyses were utilized to examine driving factors and explore improvement potential.ResultsGlobal cancer-related DALYs attributable to high BMI in older adults increased from 2.11 million in 1990 to 5.40 million in 2021, with ASDR rising from 439.99 to 497.15 per 100,000 population. Males showed greater increases despite lower ASDR. From 1990 to 2021, Asia and Africa experienced the steepest increases, while Europe and America recorded the highest ASDRs in 2021. High Socio-demographic Index (SDI) regions consistently reported the highest ASDRs in both 1990 and 2021, whereas low-middle SDI regions exhibited the most rapid increase during this period. The global ASDRs for most cancers increased from 1990 to 2021, with colorectal cancer demonstrating the highest ASDR among men and breast cancer among women in 2021. DALY growth was largely attributed to population expansion (133.04%) through decomposition analysis. Inequalities have narrowed but remained predominantly concentrated in higher SDI countries. Frontier analysis identified several high SDI countries, such as the United Arab Emirates, Slovakia, and Qatar, with substantial potential for burden reduction.ConclusionThe cancer burden attributable to high BMI in older adults has risen substantially since 1990, with marked geographic, socioeconomic, and cancer-site disparities. Targeted high BMI reduction strategies in aging populations are critical to mitigating future cancer burden and reducing inequalities.